Evidence and Lessons on the Health Impacts of Public Health Funding from the Fight against HIV/AIDS - Dillender, Marcus (American Economic Review, 2023)
HIV/AIDS has been one of the largest public health crises in recent history, and the US federal government has spent hundreds of billions of dollars fighting the disease. This study examines the impact of the large amounts of federal funding allocated to US cities to combat HIV/AIDS through the Ryan White CARE Act’s first title. The findings indicate that the cost to avoid an HIV/AIDS death through the program is roughly $334,000, that the program has saved approximately 57,000 lives through 2018, and that funding disparities are responsible for the uneven progress in combating HIV/AIDS across the United States. (JEL H51, H75, I12, I18)